2017
DOI: 10.1016/j.addr.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulating angiogenesis with integrin-targeted nanomedicines

Abstract: Targeting angiogenesis-related pathologies, which include tumorigenesis and metastatic processes, has become an attractive strategy for the development of efficient guided nanomedicines. In this respect, integrins are cell-adhesion molecules involved in angiogenesis signaling pathways and are overexpressed in many angiogenic processes. Therefore, they represent specific biomarkers not only to monitor disease progression but also to rationally design targeted nanomedicines. Arginine-glycine-aspartic (RGD) conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 209 publications
(151 reference statements)
1
48
0
Order By: Relevance
“…Nevertheless, these data may yet enable novel strategies based on αvβ3. Moreover, despite conflicting preclinical data, many studies still therapeutically target endothelial αvβ3 (reviewed in [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these data may yet enable novel strategies based on αvβ3. Moreover, despite conflicting preclinical data, many studies still therapeutically target endothelial αvβ3 (reviewed in [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Integral proteins family is associated with the upregulation of angiogenesis 108. Previous researches found that α v β 3 ‐integrin antagonist could specifically induce the apoptosis of VECs, thereby inhibiting angiogenesis and alleviating arthritis severity 109.…”
Section: Nanotherapeutics Of Ra Based On Nanodrugsmentioning
confidence: 99%
“…[107] Integral proteins family is associated with the upregulation of angiogenesis. [108] Previous researches found that α v β 3integrin antagonist could specifically induce the apoptosis of VECs, thereby inhibiting angiogenesis and alleviating arthritis severity. [109] Zhou et al recently developed a nanocarrier system translatable lipase-labile (Sn 2) fumagillin prodrug (Fum-PD) to deliver Fum, which was anticipated to improve drug retention time in the circulation, enhancing net drug delivery to angiogenic endothelial cells via "contact-facilitated drug delivery."…”
Section: Antiangiogenesis Therapymentioning
confidence: 99%
“…Finally, the tumor-targeting precision of drugs [25,26], NPs [27,28], polymers [29], biomaterials [30], or nanostructured materials [20,31,32] can be strongly improved by conjugation with peptide ligands addressing integrin receptors overexpressed by cancer cells [20,33,34]. The integrin family of cell adhesion receptors regulates a diverse array of cellular functions crucial to the initiation, progression, and metastatization of solid tumors, making them an appealing target for cancer therapy [35].…”
Section: Introductionmentioning
confidence: 99%